The Events of Frustration on Josephine in Chritie;s Crooked House Novel - Khairun Nisa; Nita Maya Valiantien; Nasrul Ullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study is aimed to find out the types of causes of frustration and defensive behaviours on Josephine’s character of Crooked House novel. There are two theories used to answer these questions such as frustrations and defensive behaviours by Krech et al. and characterization by Reaske. This study uses narrations and dialogues as the data which are taken from Crooked House novel by Agatha Christie. The results of this study find that Josephine experiences two types of causes of frustrations and conducts three types of defensive behaviours. The causes of frustrations are Josephine’s biological limitations as twelve years old girl and her social environment of living only in the Crooked House. In order to persist her existence after receiving the hard blows from her frustrations, Josephine conducts three forms of defensive behaviours which are aggression, autism, and identification. The conclusions show that Josephine’s desire to learn ballet plays the biggest role for her to experience frustrations events and due to this unfulfilled desire too that she performs the most extreme form of defensive behaviour of killing people in the Crooked House.